Depression’s double-edged impact on body mass index. A hidden catalyst for non-communicable diseases in South Africa’s aging population in long-term care facilities - Shane Naidoo; Nirmala Naidoo (PLoS ONE, 2025)
Introduction The global population of older people, who have a high prevalence of non-communicable diseases, is on an upward trajectory, notably in South Africa. The expansion of this demographic will further strain an already overwhelmed healthcare system, primarily taxed by infectious diseases in younger populations. Physical activity has been shown to effectively reduce risk factors for non-communicable diseases in older people. Objective To investigate the associations between depression, body mass index (BMI) and physical activity and its complex interplay on non-communicable diseases in older people residing in South African long-term care facilities. Method We conducted a cross-sectional study on 396 participants residing in South African rural and urban long-term care facilities to analyse BMI, waist-hip ratio, physical activity and depression levels. The Geriatric Depression Scale and the International Physical Activity Questionnaire was used to evaluate depression and physical activity respectively. Results The sample had a mean BMI of 27.53 kg/m2 (95% CI [26.99, 28.07], SD = 5.49), with an obesity prevalence of 31.82%. Additionally, 35.10% of participants exhibited some degree of depressive symptoms. In an ordinal regression model BMI was a significant predictor (B = .10, p = .007) for increases in depression. Conversely in a linear regression model, depression (B = -2.01, p = .004) and physical activity (B = -.001, p = .008) were predictors for decreases in BMI. Conclusion The relationship between depression and BMI in older people is complex, with depression often leading to both weight loss and, conversely, increased BMI contributing to a higher risk of depression. Physical activity serves as a critical intervention, helping to reduce both BMI and depressive symptoms among older people residing in long-term care facilities. This underscores the importance of integrating PA programs into care strategies to improve overall health and well-being in this population.